Peningkatan Pemahaman Penanganan Kasus Kekerasan Seksual Bagi Stakeholder Di Soloraya Berdasarkan UU TPKS - Anisah, Laili Nur (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This assistance is carried out to provide an understanding of the handling of cases of sexual violence based on the latest law, namely the Law on Crimes against Sexual Violence (TPKS). This community service is carried out in collaboration between Widya Mataram University and the Yekti Angudi Piadeging Indonesia Foundation (Yayasan Yaphi) which will present law enforcement officials and stakeholders handling and assisting victims of sexual violence cases. The method used is Participatory Active Research (PAR) which is oriented towards empowering the community to make changes. The activity was carried out in the city of Solo by presenting all Soloraya stakeholders. The results achieved from this community service are increasing understanding regarding the handling of cases of sexual violence based on the latest law, namely the Law on Crimes against Sexual Violence